Building Future-Ready Business: Technology Communication for Generation Alpha as Future Consumer - Oka Widyawati; Nyoman Basmantra (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
The rapid growth of digital technology has significantly transformed consumer behavior, particularly among Generation Alpha, who are deeply immersed in digital media from an early age. However, many businesses remain unprepared to communicate effectively with this generation, despite their increasing influence on family purchasing decisions. This study aims to analyze how technology-based communication shapes Generation Alpha’s consumer behavior using Consumer Socialization Theory (CST). A qualitative descriptive research design was employed, utilizing semi-structured interviews with Generation Alpha, their parents, and a marketing practitioner, supported by observation and documentation analysis. The findings reveal that digital media, especially TikTok and Instagram, serves as the primary socialization agent by influencing product awareness, desire formation, and evaluation through short-form content, influencers, and online reviews. Peers reinforce consumption behavior through social interaction and fear of missing out (FOMO), while parents play a crucial role as gatekeepers by controlling financial access, product safety, and purchase approval. The study concludes that consumer socialization among Generation Alpha has shifted toward media-dominated influence, highlighting the importance for businesses to adopt authentic, visually engaging, and ethically responsible digital communication strategies to remain competitive in the future.